2020
DOI: 10.1159/000506638
|View full text |Cite
|
Sign up to set email alerts
|

Lower Oxytocin Levels Are Associated with Lower Bone Mineral Density and Less Favorable Hip Geometry in Hypopituitary Men

Abstract: Introduction: Hypopituitary patients are at risk for bone loss. Hypothalamic-posterior pituitary hormones oxytocin and vasopressin are anabolic and catabolic, respectively, to the skeleton. Patients with hypopituitarism may be at risk for oxytocin deficiency. Whether oxytocin and/or vasopressin contribute to impaired bone homeostasis in hypopituitarism is unknown. Objectives: To determine the relationship between plasma oxytocin and vasopressin levels and bone characteristics (bone mineral density [BMD] and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
7
1
Order By: Relevance
“…Nevertheless, in the MINOS cohort, there was a weak significant trend for a higher fracture risk in men with a low serum OT level after adjustment for confounders including BMD and serum OT was significantly lower in men with severe osteoporosis compared to men with a normal bone status, suggesting effects of OT on other determinants of fracture risk such as muscle strength [34]. However, in another cross-sectional study including 37 hypopituitary men without any previous history of fracture or any medication for osteoporosis, there was a robust positive association between fasting OT serum levels and BMD (Z-scores at the lumbar spine, femoral neck and total hip) and favorable hip geometry and strength variables at the intertrochanteric region in men with central diabetes insipidus but not in men with anterior pituitary deficiencies [36].…”
Section: Oxytocin and Osteoporosis: Human Datamentioning
confidence: 94%
“…Nevertheless, in the MINOS cohort, there was a weak significant trend for a higher fracture risk in men with a low serum OT level after adjustment for confounders including BMD and serum OT was significantly lower in men with severe osteoporosis compared to men with a normal bone status, suggesting effects of OT on other determinants of fracture risk such as muscle strength [34]. However, in another cross-sectional study including 37 hypopituitary men without any previous history of fracture or any medication for osteoporosis, there was a robust positive association between fasting OT serum levels and BMD (Z-scores at the lumbar spine, femoral neck and total hip) and favorable hip geometry and strength variables at the intertrochanteric region in men with central diabetes insipidus but not in men with anterior pituitary deficiencies [36].…”
Section: Oxytocin and Osteoporosis: Human Datamentioning
confidence: 94%
“…Data regarding oxytocin deficiency in patients with panhypopituitarism or CDI are scarce. Thus, the need for replacement treatment remains mainly theoretical, although a cross‐sectional study demonstrated that low oxytocin levels were associated with lower bone mass density and less favourable hip geometry, 152 as well as with cognitive impairment. Preliminary results provide some evidence of potential benefits of oxytocin therapy with respect to improving these deficits and accompanying metabolic disturbances 153,154 .…”
Section: Treatmentmentioning
confidence: 99%
“…OT and VP are anabolic and catabolic, respectively, to the skeleton. Patients with high fasting OT levels also have high bone mineral density [153]. In schizophrenic patients, the numerical density of OT degrading enzyme insulin-regulated aminopeptidase-expressing neurons in the PVN and the suprachiasmatic nuclei is significantly reduced, which might be associated with the reduction in neurophysin-containing neurons in these nuclei in schizophrenia [154].…”
Section: Ot/otr Signaling In the Health And Maternal Chronic Social S...mentioning
confidence: 99%